Impulse control disorders and use of dopamine agonists in early onset Parkinson’s disease - Turcano, Pierpaolo; Jacobson, Jessie; Ghoniem, Khaled; Mullan, Aidan; Camerucci, Emanuele; Stang, Cole; Piat, Capucine; Bower, James H.; Savica, Rodolfo (Frontiers in Neurology, 2024)
Introduction Impulse control disorders (ICDs) are defined as excessive and repetitive behaviors that may affect Parkinson’s disease (PD) patients exposed to dopamine agonists. Current data on ICDs in patients with early-onset Parkinson’s disease (EOPD) is lacking. In this study we aim to assess the frequency of use of dopamine agonists, the prevalence of ICDs, and to explore potential factors associated with their development in patients with EOPD. Methods We used the Mayo Clinic Data Explorer system to investigate a population-based cohort of EOPD patients between 1990 and 2022 at Mayo Clinic, Rochester, MN. We used ICD coding for parkinsonism; then, we reviewed all the clinical records and included only those patients with a clinical diagnosis of PD with symptoms onset at or before the age of 50, and who developed ICDs after using therapeutic doses of dopamine agonists. Results A total of 831 (513 males and 318 females) patients with EOPD were included with a median age at symptom onset of 42 years of age (CI: 37–46). Dopamine agonists were used in 49.7% of all patients; of these, only 14.5% developed symptoms of one or more ICDs. Hypersexuality was the most commonly observed ICD (38.3%), and the only one having a statistically significant male predominance (p = 0.011). Conclusion ICDs are common in EOPD, particularly when associated with the use of dopamine agonists.